2018
DOI: 10.1371/journal.pone.0190900
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus application reduces aluminum toxicity in two Eucalyptus clones by increasing its accumulation in roots and decreasing its content in leaves

Abstract: Under acidic conditions, aluminum (Al) toxicity is an important factor limiting plant productivity; however, the application of phosphorus (P) might alleviate the toxic effects of Al. In this study, seedlings of two vegetatively propagated Eucalyptus clones, E. grandis × E. urophylla ‘G9’ and E. grandis × E. urophylla ‘DH32-29’were subjected to six treatments (two levels of Al stress and three levels of P). Under excessive Al stress, root Al content was higher, whereas shoot and leaf Al contents were lower wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 57 publications
(68 reference statements)
1
11
0
Order By: Relevance
“…Similar results were also obtained by QTL mapping for Al 3+ tolerance in common bean [68]. Recent research has shown that phosphorus application could reduce aluminum toxicity [69]. Taken together, these results demonstrated that there are some QTLs in the colocalized intervals that may be associated with Al 3+ tolerance and P stress in soybean.…”
Section: Discussionsupporting
confidence: 82%
“…Similar results were also obtained by QTL mapping for Al 3+ tolerance in common bean [68]. Recent research has shown that phosphorus application could reduce aluminum toxicity [69]. Taken together, these results demonstrated that there are some QTLs in the colocalized intervals that may be associated with Al 3+ tolerance and P stress in soybean.…”
Section: Discussionsupporting
confidence: 82%
“…A large number of strategies have been explored to mitigate the Al toxicity in plants to acid soils. Most of the strategies can be divided into two classes: inorganic amendments such as exogenous application of mineral elements including Ca, Mg, P, S, B, and Si and ground oxide/hydroxide [ 111 , 112 , 113 , 114 , 115 , 116 , 117 ] ( Table 4 and Table 5 ) and organic amendments such as organo-mineral fertilizers, plant growth promoting bacteria (PGPB), green waste compost, plant-derived biochars, and their combination with other minerals [ 118 , 119 ] which played a pivotal role in Al toxicity alleviation in plants to acid soils. Conversely, we did not observe considerable existing literatures concerning the role of K, Mn, Zn, and Mo in Al toxicity alleviation in plants though these are essential minerals.…”
Section: Role Of Mineral Nutrition For Mitigating Aluminum Toxicitmentioning
confidence: 99%
“…The recommendation for twice-a-day irrigation frequency can also be reinforced by the best performance observed for the root dry mass parameter ( Table 2). The more abundant the root system is, the greater the chance of survival of the seedling in the field, regardless of its height, so root dry mass is an important indicator of seedling quality, which is directly related to the survival and initial growth of the seedling (MENDONÇA et al, 2016;TENG et al, 2018). In this context, the greater root dry mass produced in the treatment with frequency of two irrigations per day is evidence of the potential of this water management for the production of eucalyptus seedlings.…”
Section: Discussionmentioning
confidence: 99%